2020
DOI: 10.1017/dmp.2020.131
|View full text |Cite
|
Sign up to set email alerts
|

Working During Pandemic Disasters: Views and Predictors of EMS Providers

Abstract: Objective: This study aims to assess the perception and attitude of Emergency medical services (EMS) providers toward working during disease outbreaks, and the factors that may influence their decisions to ultimately work or not. Methods: This is a cross-sectional study assessing the attitude of EMS providers to work during disease outbreaks. Descriptive statistics and regression analyses were performed to assess attitudes towards reporting for duty and factors that influence providers’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 19 publications
1
48
0
2
Order By: Relevance
“…Previous research investigating the impact of infectious diseases outbreaks (e.g. COVID-19, Ebola virus disease, Severe acute respiratory syndrome, influenza and Middle East respiratory syndrome) has shown that while emergency department (ED) presentations decreased [6] , [7] , [8] , [9] , emergency nurses and physicians and paramedics faced increased stress and anxiety [10] , [11] , fear of being stigmatised from family and society due to the nature of their work [12] , and had elevated concerns for the safety of their families [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research investigating the impact of infectious diseases outbreaks (e.g. COVID-19, Ebola virus disease, Severe acute respiratory syndrome, influenza and Middle East respiratory syndrome) has shown that while emergency department (ED) presentations decreased [6] , [7] , [8] , [9] , emergency nurses and physicians and paramedics faced increased stress and anxiety [10] , [11] , fear of being stigmatised from family and society due to the nature of their work [12] , and had elevated concerns for the safety of their families [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…The review of the studies in the literature on Covid-19 demonstrated that the number of studies conducted on prehospital EMS professionals is not many. The participation rate of EMS professionals in studies conducted with healthcare professionals is low (Alwidyan et al, 2020). This is due to the fact that they do not have enough time because they work in the field and they are not easily accessible.…”
Section: Discussionmentioning
confidence: 99%
“…However, healthcare workers continued to work nonstop and are faced with critical situations. Especially at the beginning, the insufficiency of the measures for the pandemic, and the lack of guidelines on functioning negatively affected this process (Alwidyan et al, 2020). Among these are the risk of catching the Covid-19 virus and spreading it to their immediate surroundings, experiencing the symptoms that develop due to catching the virus, the possibility of not taking adequate protection measures at the scene, and their physical and mental health's being adversely affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review by Devnani indicated that being male is a predictor of being more willing to work during pandemics (31). In contrast, a recent study on Jordanian paramedics found no significant gender differences to work during pandemic disasters (32). Furthermore, when it comes to working during the COVID-19 pandemic, no gender differences were found in healthcare workers' willingness to care for COVID-19 patients (33)(34)(35).…”
Section: Predictors Of Willingness To Care For Covid-19 Patientsmentioning
confidence: 99%